PREVALENCE OF TOXOPLASMA GONDII ANTIBODIES IN CATS IN URMIA, NORTHWEST OF IRAN - S. Raeghi; S. Sedeghi; S Sedeghi (Journal of Animal and Plant Sciences, 2011)
Toxoplasma gondii is a zoonotic protozoan parasite found worldwide and cause a disease known as toxoplasmosis. Cats are the natural reservoir of Toxoplasma gondii and excrete the resistant oocysts in the environment. Toxoplsamosis is an important disease in neonates and immune disorder patients. In the present study, the presence of T. gondii antibodies was examined in 130 stray and household referred cats to private animal clinics and veterinarian hospital in Urmia, center of west Azerbaijan province, from October-2008 to January 2010 by modified agglutination test (MAT). T. gondii antibodies were detected in 46 (35.3%) cats. The antibody titers in positive animals ranged from 1:20-1:1280. No statistically significant difference was observed between male & female cats and there was relationship between seropositivity and age. Only 3 cats were shedding T.gondii-like size oocysts that they were seronagative with MAT. This study suggested that T.gondii was widespread in stray and household cats in Urmia, therefore, it is essential to control the cats and use an integrated sanitary approach.
Keywords: Toxoplasma gondii. Cat. MAT. Urmia. Iran